2007
DOI: 10.1063/1.2741408
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-based growth and magnetic properties of inhomogeneous Cu-doped ZnO nanocrystals

Abstract: The authors report on the ferromagnetic ordering in 1.86at.% Cu-doped ZnO nanocrystals synthesized by a solvothermal route. The distribution of Cu in ZnO lattice was inhomogeneous. In the Cu-poor cores, a spin-split acceptor impurity band model was proposed to explain the ferromagnetism. While in the Cu-rich surface layers, the shallow donorlike defects generated by imperfect oriented attachment could not only compensate a few holes but also readily occupy the Cu 3d states to destroy CuO4 tetrahedra, hence res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
47
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 34 publications
8
47
0
Order By: Relevance
“…The saturation magnetizations are about 0.24 μB/Cu 2+ (0.51 emu/g) and 0.26 μB/ Cu 2+ (0.55 emu/g) at 5 K and 300 K, respectively. Thus saturation magnetization is higher than the results of previous report [30]. Besides, we note that the saturation magnetization, remanent magnetization, and coercivity at 300 K are very close to those of at 5 K. Therefore, it can be concluded that the Curie temperature of this samples are above 300 K.…”
Section: +supporting
confidence: 54%
“…The saturation magnetizations are about 0.24 μB/Cu 2+ (0.51 emu/g) and 0.26 μB/ Cu 2+ (0.55 emu/g) at 5 K and 300 K, respectively. Thus saturation magnetization is higher than the results of previous report [30]. Besides, we note that the saturation magnetization, remanent magnetization, and coercivity at 300 K are very close to those of at 5 K. Therefore, it can be concluded that the Curie temperature of this samples are above 300 K.…”
Section: +supporting
confidence: 54%
“…953.17 eV, respectively, similar to the result of Cu-doped ZnO nanocrystals. [14,25] Some satellite peaks are associated with these two peaks. A Gaussian fitting determines the ratio of Cu 2þ /Cu 1þ to be 80.4:19.6, in good agreement with the results of previous reports.…”
mentioning
confidence: 97%
“…A Gaussian fitting determines the ratio of Cu 2þ /Cu 1þ to be 80.4:19.6, in good agreement with the results of previous reports. [14,25] Unlike Cu 2þ , Cu 1þ has fully filled 3d orbitals (3d 10 4s 0 ) and hence does not contribute to ferromagnetism.…”
mentioning
confidence: 99%
“…40 Cu 2p3/2 and 2p1/2 core levels of the sample were fitted with Gaussian functions and centered at 933.7 and 953.5 eV, respectively, implying that Cu is in a divalent valence state, which is good agreement with the other studies in the literature. 41,42 Furthermore, a satellite peak is observed at binding energies in the range of 940-945 eV. CuO (Cu 2þ ) differs from metallic copper (Cu 0 ) and Cu 2 O (Cu 1þ ) because Cu 2þ is known to have Cu 2 p satellite peaks at higher binding energy associated with the existence of Cu 3 d hole states (Cu 3 d 9 ).…”
Section: Resultsmentioning
confidence: 99%